REVIEWS (Heythrop journal, 1971)
Aristotele. La Metafisica. Traduzione, introduzione, commento a cura di Giovanni Reale. Vol. I God and the Empiricists. By Harry R. Klocker. The Elusive Mind. By H. D. Lewis. Absolute Value. A study in Christian Theism. By Dom Illtyd Trethowan. Human Values and Christian Morality. By Josef Fuchs, s.j. Three Issues in Ethics. By John Macquarrie. Conflict of Ideals: Changing Values in Western Society. By Luther J. Binkley. The Philosophy of Martin Buber. Edited by Paul Arthur Schilpp and Maurice Friedman. Augustine the Theologian. By Eugene TeSelle. Stephanus de Lingua-tonante: Studies in the Sermons of Stephen Langton. By Phyllis Barzillay Roberts. The Monastic Theology of Aelred of Rievaulx. By Amédée Hallier. The Great Schism 1378: The Disintegration of the Papacy. By John Holland Smith. Alexander III and the Twelfth Century. By Marshall W. Baldwin. A Social and Religious History of the Jews. Volumes XIII, XIV: Late Middle Ages and Era of European Expansion. By Salo Wittmayer Baron. The Yahwist. The Bible's First Theologian. By Peter Ellis, c.ss.r. A Study of the Psalms of Ascents. By Cuthbert C. Keet. Death and Immortality. By Joseph Pieper. The Nature and Destiny of Man. By J. R. Surcher. The Trinity. By Karl Rahner. Translated by Joseph Donceel. Christ and Church. By M. J. Le Guillou. New Testament Questions of Today. By Ernst Kasemann.